CMOS Circuits for Biological Sensing and Processing (Springer International Publishing, 2018)
This book provides the most comprehensive and consistent survey of the field of IC design for Biological Sensing and Processing. The authors describe a multitude of applications that require custom CMOS IC design and highlight the techniques in analog and mixed-signal circuit design that potentially can cross boundaries and benefit the very wide community of bio-medical engineers. Provides a single-source reference to the state-of-the-art in analog and mixed-signal circuit design for biological and chemical sensing; Highlights numerous applications, categorized as Ex-vivo, In-vivo, and Wearable and Technology Trends; Explains basic details of the circuits used in a very consistent manner, identifying clearly the CMOS and non-CMOS technologies used, along with the method to interact with the transducer (various kinds of electrodes, ion-sensitive layers, Carbon nanotubes etc.).